Factors influence the implementation of lean accounting in mechanical firms - Thuy, Tran Thi Thu; Dao, Phan Thi Anh; Quang, Dang Van; Tam, Mai Thi; Tai, Do Duc (Edelweiss Applied Science and Technology, 2025)
The purpose of this study focuses on quantitatively analyzing factors influencing the implementation of lean accounting at mechanical firms in Hanoi through the results of linear regression analysis with the support of SPSS software. We surveyed 560 employees working at mechanical firms in Hanoi, collecting 450 questionnaires, reaching a rate of 80.3%; after cleaning, 395 questionnaires met the standards for use in the next steps. The research results show that the seven identified factors all have a positive influence on the implementation of lean accounting in mechanical firms, in which the order of influence of the factors on the implementation of lean accounting in mechanical firms in decreasing order is qualification and awareness of accounting staff (KT), digital technology (CNS), level of competition (MDCT), qualification and awareness of managers (NQL), size (QM), cost of organizing lean accounting (CPTC), and management decentralization (PCQL). From the research results, the authors have proposed a number of recommendations to improve the implementation of lean accounting in mechanical firms, thereby contributing to the improvement of lean production and improving the business performance of mechanical firms in the coming time.